Efficacy of antibody levels in different post-exposure rabies vaccination programs - Kaya Kilic, Esra; Bulut, Cemal; Sonmezer, Meliha Cagla; Ataman Hatipoglu, Cigdem; Kinikli, Sami; Demiroz, Ali Pekcan (The European Research Journal, 2016)
Objectives. Rabies is a fatal acute viral zoonotic disease causing encephalomyelitis in humans and many other mammalian animals. Prophylaxis is vital since there is no treatment for rabies. This study was a comparison of antibody levels in patients who were vaccinated following different vaccinationprotocols. Methods. Eighty-five patients who were included in the rabies vaccination program who presented to the vaccination center of our clinic with the complaint of suspicious contact with rabies were included the study. In 61 (71.8%) patients a 2-1-1 vaccine program (Zagreb regimen) was implemented, and in 24 (28.2%) patients, a 5-dose rabies vaccine and rabies immune globulin (RIG) in a dose of 40 IU/kg (Essen regimen) was applied. Results. In patients on the 2-1-1 vaccine program, antibody levels on the 21st day were greater than 0.5 IU/ml in 49 (80.3%) patients. Antibody levels on the 28th day in the group that received the 5-dose rabies vaccine and rabies immune globulin administration was greater than 0.5 IU/ml in 17 (70.8%) patients. The difference between the two groups of vaccination programs was not statistically significant (p=0.344). Seroconversion rates for approximately one month after the last dose of vaccination in the serum samples were 90% and 75% in the groups with 2-1-1 vaccination, and RIG and 5-dose vaccinations, respectively. The differences were not statistically significant (p=0.071). Conclusions. Identification of similar seroconversion rates suggests that the 2-1-1 vaccination program may be a good alternative option to the standard vaccination program when RIG is unavailable.